Potentials and challenges of involving indigenous communities in ecotourism in Belum-Temenggor Forest Complex, Perak, Malaysia - Abdullah, Azreen Rozainee; Chan, Ngai Weng; Mohamed, Badaruddin (2013)
Ecotourism is usually regarded as responsible travel to nature-based areas with the aims to enjoy nature while at the same time to contribute towards the protection and conservation of nature as well as to the welfare of local communities in that area. Most significantly, ecotourism should provide opportunity for the locals to participate and gain benefit from its development. Belum Temengor forest is among the most promising ecotourism destinations in Malaysia. Furthermore, this area is currently widely being promoted up to international level due to its complex ecosystem and rich wildlife diversity. Not only blessed with rich and flourishing flora and fauna, this area also shelters the indigenous orang asli communities made up of Jahai and Temiar together with their unique cultures. However, the main research questions explored in this paper are: Are these ‘shy’ indigenous communities prepared to delve into the fast developing ecotourism sector? How are they involved in ecotourism and do they benefit from it? This paper examines how the orang asli perceive ecotourism and its development, and how ecotourism in turn affects them. The main research instrument used is qualitative techniques based on interviews with key informants. Results indicate that the BTFC is facing increasing threats, and tourism development is threatening its natural heritage. The results also show that ecotourism has great potentials but the orang asli community enjoys little of the tourism benefits. Instead, orang asli cultures are eroded, their natural habitat on which they rely on for their subsistence increasingly destroyed, and their villages encroached upon. Ecotourism needs to find a balance between economics, environment and social equity, viz. where the orang asli community is involved and enjoys equally the benefits to ensure its sustainability in BTFC.